Effect of Cr on microstructure and corrosion resistance of copper-nickel alloys fabricated by selective laser melting - GAO Shiyang; HE Xing; ZHANG Mina; CHEN Haida; ZHOU Shudong; WANG Yishen; DING Jie (Fenmo yejin jishu)
To enhance the mechanical properties and corrosion resistance of the copper-nickel alloys, the mechanical alloying was employed to introduce Cr powders with the mass fraction of 0%~3% into CuNi30 matrix powders, and the CuNi30-xCr copper-nickel bulk alloys (x is mass fraction, x=0, 1%, 2%, 3%) were fabricated by selective laser melting technology with the relative densities exceeding 98%. The influences of Cr mass fraction on the microstructure, mechanical properties, and corrosion resistance of the copper-nickel bulk alloys were systematically investigated by optical microscopy, X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, and electrochemical workstation analysis. The optimization mechanism of Cr on the mechanical properties and the regulatory mechanism on the corrosion behavior of the alloys were elucidated. In the results, a small amount of Cr can solidify into the α-Cu phases during the laser melting process, and increasing the Cr content can promote the precipitation of Cr-rich phases. The addition of Cr elements improves the mechanical properties and corrosion resistance of the copper-nickel alloys with the microhardness increasing from HV0.2 126 to HV0.2 157 as the Cr content increases. When the Cr content is 3%, the corrosion potential of the alloys shifts positively from −0.238 V (CuNi30) to −0.210 V (reference electrode is saturated calomel electrode), and the corrosion current density decreases from 1.38×10−6 A·cm−2 to 7.72×10−7 A·cm−2, showing the reduction of 44%, due to the solid solution strengthening of Cr and the formation of Cr-rich second phases, inhibiting the matrix anodic dissolution tendency.